2014
DOI: 10.1016/j.comppsych.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and psychosocial differences in psychiatrically hospitalized military service members with single versus multiple suicide attempts

Abstract: Marjin, "Diagnostic and psychosocial differences in psychiatrically hospitalized military service members with single versus multiple suicide attempts" (2014

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…We found that the two groups did not differ on any of the demographic characteristics. This is broadly similar to previous reports from India[ 10 ] and the West[ 9 23 ] and suggests that the demographics of repeat attempters tend to remain uniform across various ethno-cultural settings. Only a few studies have reported a female preponderance among multiple attempters.…”
Section: Discussionsupporting
confidence: 89%
“…We found that the two groups did not differ on any of the demographic characteristics. This is broadly similar to previous reports from India[ 10 ] and the West[ 9 23 ] and suggests that the demographics of repeat attempters tend to remain uniform across various ethno-cultural settings. Only a few studies have reported a female preponderance among multiple attempters.…”
Section: Discussionsupporting
confidence: 89%
“…Despite growing concerns about suicide among military personnel, however, only a few studies have examined the issue of multiple attempter status in this population. Similar findings were recently reported in a sample of psychiatrically hospitalized military personnel (Kochanski-Ruscio et al, 2014). Similar findings were recently reported in a sample of psychiatrically hospitalized military personnel (Kochanski-Ruscio et al, 2014).…”
supporting
confidence: 91%
“…Nine studies reported an association between alcohol or drug use/dependence and suicidal attempts (67,93) and suicide mortality (75,77,81,87,88,96,103). This association was found across a range of populations including general population samples (67,77,87,96), elderly individuals (103), soldiers/veterans (88,93), patients discharged from a psychiatric facility ( 81), and patients with major depressive disorder (75). Five studies (75,81,87,88,93) examined both alcohol and drug use disorders, one study assessed substance abuse (96) and one study measured alcohol use disorders (103).…”
Section: Mental Health Problems/psychiatric Illnessmentioning
confidence: 99%